Sugarcane - Technology and Research 2018
DOI: 10.5772/intechopen.72300
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Nutrition and Fertilization of Sugarcane

Abstract: Sugarcane extracts large amounts of nutrients from the soil and accumulates them in the plant due to its large mass production. Thus, agricultural practices ensuring adequate supply of nutrients to the crop must be adopted to obtain high crop yields in the cane plant cycle and small decreases in the subsequent cycles. In this chapter, the following items will be addressed and discussed: soil sampling, soil fertility evaluation, liming, plastering, cane plant chemical fertilization, sprout chemical fertilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(117 citation statements)
references
References 6 publications
2
52
0
22
Order By: Relevance
“…Following the recommendation of Ref. [1], 5.0 t of dolomitic limestone and 1.5 t of gypsum were applied per ha in September of the year prior to the planting of sugarcane. The soil was plowed and harrowed, followed by the sowing of Crotalaria juncea.…”
Section: Agroindustrial Morphological and Tolerance Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the recommendation of Ref. [1], 5.0 t of dolomitic limestone and 1.5 t of gypsum were applied per ha in September of the year prior to the planting of sugarcane. The soil was plowed and harrowed, followed by the sowing of Crotalaria juncea.…”
Section: Agroindustrial Morphological and Tolerance Characteristicsmentioning
confidence: 99%
“…In evaluations carried out in small properties of the Zona da Mata region, the authors found that to produce 120 tons of natural matter per ha (about 100 t of industrializable culms), the accumulation of nutrients in shoots is approximately 150, 40, 180, 90, 50, and 40 kg of N, P, K, Ca, Mg, and S, respectively. In the case of iron, manganese, zinc, copper, and boron, accumulation in shoot biomass for a production of 120 t is around 8.0, 3.0, 0.6, 0.4, and, 0.3 kg, respectively [1]. Because of this high nutrient removal, it is necessary to know the nutrient supply capacity of the soil to complement it with fertilization if necessary.…”
Section: Evaluation Of Soil Fertility and Lime And Gypsum Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to setting up the study, a chemical analysis of the soil w as carried out at depths of 0 to 20 and 20 to 40 cm. With the results, dolomitic limestone and plaster w ere applied in a proportion of 3:1, and in sufficient quantity to raise base saturation to 60% in the topsoil layer and reduce aluminum saturation on the subsurface, as proposed by Oliveira et al (2007) and Raij (2011). After 60 days, the soil w as plow ed, harrow ed, and subsequently furrow ed.…”
Section: Methodsmentioning
confidence: 99%